качество воды в родниках города перми (по материалам 2002-2007 гг.) (Географический вестник=Geographical bulletin, 2017)
Дана оценка качества воды в родниках левобережной части г. Перми и Кировского района, расположенного на правом берегу р. Камы. Анализ качества воды представлен по материалам 2002 – 2007 гг.QUALITY OF WATER IN SPRINGS OF THE PERM (ON MATERIALS 2002-2007 YEARS)The condition of springs in a left-bank part of city ofPermis a little bit worse, than in Kirovsk area. Relative density of non-standard tests of spring water in a left-bank part of city almost in 1,5 times is more, than in right-bank. Excess of maximum concentration limit is marked on 11 of 25 studied parameters on left protect cities, in Kirovsk area - on three.